Policing sexuality sex, society, and the state - Lee, Julian C. H. (Strategic Information and Research Development Centre, 2011)
Policing Sexuality explores the regulation of sexual behavior and identity by nation states, and will question how and why states have sought to influence and control the sexuality of their citizens. This unique book simultaneously introduces the topic and argues for interpretation of state policing of sexuality. The author presents both theoretical and ethnographic literature, distilling common themes and causes and presenting factors that contribute towards a state's desire to control both the sexual behavior and sexual identity of its citizens, such as the influence of colonialism, class, religion, and national identity. This book features five crucial case studies from India, Britain, the USA, Malaysia, and Turkey. Policing Sexuality illuminates this fascinating study with comparative accounts.